1980
DOI: 10.1083/jcb.86.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Identification of membrane proteins mediating the interaction of human platelets

Abstract: Membrane glycoproteins that mediate platelet-platelet interaction were investigated by identifying those associated with the cytoskeletal structures from aggregated platelets . The cytoskeletal structures from washed platelets, thrombin-activated platelets (platelets incubated with thrombin in the presence of mM EDTA to prevent aggregation) and thrombinaggregated platelets (platelets activated in the presence of mM Ca") were prepared by first treating platelet suspensions with 1% Triton X-100 and 5 mM EGTA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
190
3
3

Year Published

1982
1982
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(210 citation statements)
references
References 57 publications
14
190
3
3
Order By: Relevance
“…We further demonstrated that these proteins can be crosslinked to one another in intact and detergent-extracted membranes by protein crosslinking agents (29). In addition, other work indicates that stimuli such as concanavalin A or thrombin can under the appropriate conditions induce a large increase in the total surface GPIIb and III (which bind concanavalin A [24]) recovered in the Tritoninsoluble cytoskeleton (30,35). These results indicated that even in the resting platelet membrane, a subfraction of GPIIb and III that accounted for -10 to 15 % of the total was already associated with the Triton-insoluble fraction of isolated membranes.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…We further demonstrated that these proteins can be crosslinked to one another in intact and detergent-extracted membranes by protein crosslinking agents (29). In addition, other work indicates that stimuli such as concanavalin A or thrombin can under the appropriate conditions induce a large increase in the total surface GPIIb and III (which bind concanavalin A [24]) recovered in the Tritoninsoluble cytoskeleton (30,35). These results indicated that even in the resting platelet membrane, a subfraction of GPIIb and III that accounted for -10 to 15 % of the total was already associated with the Triton-insoluble fraction of isolated membranes.…”
mentioning
confidence: 90%
“…Finally, the GPIIb-III membrane actin complex bound with high efficiency to rabbit f-actin in vitro in a Ca++-independent manner, whereas the monomeric forms found in the Triton-soluble fraction did not bind to actin. These results indicate that two forms of GPllb and III exist: one that binds directly to endogenous membrane actin and one that does not.Numerous studies have provided largely indirect evidence for transmembrane interactions among surface proteins and receptors of cells and an internal membrane matrix composed of actin and other cytoskeletal proteins (3,5,7,10,14,16,17,19,23,25,27,31,35,40,45). Indeed, a number of studies have shown that the surface topography and lateral mobility of receptors can be modulated by the underlying cytoskeleton and its associated contractile and motile elements (20,28,30,31,36,37,39).…”
mentioning
confidence: 99%
“…In addition, the ratio of filamentous to non-filamentous actin was determined by separation of proteins insoluble of soluble in Triton X-100, respectively (22). After treatment of hepatocytes with or without osmotic stress or with toxins, respectively, the cells were lysed by addition of an ice cold Triton solution containing 20 g/1 Triton X-100, 160 mmol/1 KC1, 20 mmol/1 EGTA, 8 mmol/1 sodium azide, and 40 mmol/1 imidazole HC1, pH 7.O.…”
Section: Measurement Of Cellular G-actin F-actin and Of Proteinmentioning
confidence: 99%
“…Cytoskeletal fractions were prepared by using a modification of the method described by Phillips et al [2]. Briefly, platelet suspensions (1.5 ml) were lysed before or at various intervals after agonist addition by adding equal volumes of ice-cold 2 x Triton lysis buffer (pH 7.5) containing 100 mM Tris-HCl, 2% Triton X-100, 10 mM EGTA, 10 mM EDTA, 2 mM sodium orthovanadate, 20 mM leupeptin, 2 rnM phenylmethylsulfonyl fluoride, 20,uM pepstatin A and 0.56 trypsin inhibitor unit (t.i.u.…”
Section: Preparation Of Platelet Eytoskeleton and Membrane Skeletonmentioning
confidence: 99%
“…Several regulatory proteins in platelets are known to associate with the actin-rich cytoskeleton in a manner dependent on activation and cross-linking of the integrin e.uB3. These include the integrin %tf13 itself [2][3][4][5], protein tyrosine kinases such as pp60 st" [6--12] and pp60 c-v~s [12], the protein tyrosine pbosphatase SH-PTP1 [13], small molecular weight GTP-binding proteins like Rho A [14], RaplB [15,16], Rap2B [17] and CDC42Hs (submitted for publication) and other signalling proteins [6,7]. This complex of specific signalling proteins might regulate integrinactin interaction in aggregating platelets.…”
Section: Introductionmentioning
confidence: 99%